The course of vocational functioning in patients with schizophrenia: Re-examining social drift - Gabriela Vargas; Martin Strassnig; Samir Sabbag; Felicia Gould; Dante Durand; Laura Stone; Thomas L. Patterson; Philip D. Harvey (Schizophrenia Research: Cognition, 2014)
Vocational functioning is markedly impaired in people with schizophrenia. In addition to low rates of employment, people with schizophrenia have been reported to be underachieved compared to other family members. Among the causes of this vocational impairment may be cognitive deficits and other skills deficits, as well as social factors impacting on opportunities for employment. In this study, we examined two separate samples of people with schizophrenia who differed in their educational and social backgrounds. We compared personal and maternal education in people with schizophrenia attending an outpatient rehabilitation facility (n = 57) or receiving outpatient services at a VA medical center (n = 39). The sample as a whole showed evidence of decline in vocational status from their best job to their most recent job. Patients attending a rehabilitation facility had completed less education than their mothers, while the VA patients completed more. Differences between personal and maternal education predicted the difference in status between best and latest jobs in the sample as a whole. VA patients were more likely to be living independently and performed better on a measure of functional capacity than the rehabilitation sample. These data implicate vocational decline in schizophrenia and also suggest that this decline may originate prior to the formal onset of the illness. At the same time, vocational outcomes appear to be related to social opportunities.